Abuse-deterrent formulations and opioid-related harms in North Carolina, 2010-2018 - DiPrete, Bethany L; Dasgupta, Nabarun; Oh, G Yeon; Moga, Daniela C; Slavova, Svetla; Slade, Emily; Delcher, Chris; Pence, Brian W; Ranapurwala, Shabbar I (American journal of epidemiology, 2025)
Abuse-deterrent formulations of opioid analgesics (ADFs) were introduced to reduce opioid-related harms among pain patients, but postmarketing study results have been mixed. However, these studies may be subject to bias from selection criteria, comparator choice, and potential confounding by “indication,” highlighting the need for thorough study design considerations. In a sample of privately insured patients prescribed ADF or non-ADF extended-release/long-acting (ER/LA) opioids in North Carolina, we implemented a version of the prevalent new-user design to evaluate the relationship between ADFs and opioid use disorder (OUD, n = 235) and opioid overdose (n = 18) through 6 months of follow-up using inverse probability-weighted cumulative incidence functions and Fine-Gray models. The weighted hazard ratio (HRw) of opioid overdose among patients initiating ADFs was 0.87 (95% CI, 0.23-3.24) times as high as among patients who initiated, restarted, or continued non-ADF ER/LA opioids. We observed a short-term benefit of ADFs for incident OUD (HRw = 0.58; 95% CI, 0.35-0.93) compared to non-ADF ER/LA opioids in the first 6 weeks of follow-up, but this benefit disappeared later in follow-up (HRw = 1.30; 95% CI, 0.86-1.95). In summary, our findings add to the expanding body of evidence that there is no clear long-term reduction in harm from ADF opioids among patients in outpatient use. This article is part of a Special Collection on Pharmacoepidemiology.